(untitled) (Journal of Computational Mathematics, 2021)
In this paper, we present a dual algorithm for minimizing a convex quadratic function with two quadratic constraints. Such a minimization problem is a subproblem that appears in some trust region algorithms for general nonlinear programming. Some theoretical properties of the dual problem are given. Global convergence of the algorithm is proved and a local superlinear convergence result is presented. Numerical examples are also provided.